Critically modern : alternatives, alterities, anthropologies - Knauft, Bruce M. (Indiana University Press, 2002)
Annotation Are there multiple ways of being "modern" in the world today? How do people in various parts of the world become modern in their own distinct ways? Does the current focus on modernity in the social sciences resurrect a series of dichotomies ("traditional" and "modern, " "the West" and "the Rest, " "developed" and "undeveloped") that social theorists have sought to move beyond in recent years? Or do inflections of modernity capture key features of ideology and influence in the contemporary world? Combining rich ethnographic analysis with incisive theoretical critiques, this timely volume is certain to make an important mark in anthropology and in all related fields in which modernity is a central problematic.
Revisions of papers presented at a special session held at the 2000 meeting of the American Anthropological Association in San Francisco.
Keywords: Social change -- Cross-cultural studies.; Civilization, Modern -- Cross-cultural studies.; Acculturation -- Cross-cultural studies.; Changement social -- Études transculturelles.; Modernité -- Études transculturelles.; Acculturation -- Études transculturelles.; SOCIAL SCIENCE -- General.; Acculturation; Civilization, Modern; Social change; Moderniteit.; Cross-cultural studies; Congressen (vorm)